2011
DOI: 10.1111/j.1365-2664.2011.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

Could our fisheries be more productive? Indirect negative effects of bottom trawl fisheries on fish condition

Abstract: Summary1. The nets used in bottom trawl fisheries cause mortality of benthic invertebrates and this can decrease the long-term availability of prey to exploited fish species by reducing the abundance of benthic invertebrates. This may have consequences for the sustainability of fisheries. 2. We assessed the impact of bottom trawling on the food availability of fish by comparing the condition of fish (as weight-at-length) in an area that had a steep commercial bottom-trawling gradient in the Irish Sea but other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 39 publications
0
82
2
Order By: Relevance
“…2) and thus juveniles and young adults could be benefitting from reduced competition as well as the proliferation of benthic prey species. On the contrary, the effect of fishing effort on body condition of recruits of P. blennoides was negative, which could be explained by a reduction of their main prey as v www.esajournals.org observed in the recruitment grounds of other areas (Hiddink et al 2011). Local effects of fishing effort on recruits of M. merluccius and M. poutassou present a consistent latitudinal gradient, with stations north and south of the Balearic Islands showing contrasting responses in body condition.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…2) and thus juveniles and young adults could be benefitting from reduced competition as well as the proliferation of benthic prey species. On the contrary, the effect of fishing effort on body condition of recruits of P. blennoides was negative, which could be explained by a reduction of their main prey as v www.esajournals.org observed in the recruitment grounds of other areas (Hiddink et al 2011). Local effects of fishing effort on recruits of M. merluccius and M. poutassou present a consistent latitudinal gradient, with stations north and south of the Balearic Islands showing contrasting responses in body condition.…”
Section: Discussionmentioning
confidence: 85%
“…The impact of trawling disturbance on the marine environment has been widely investigated, evidencing mostly negative effects from populations to ecosystems properties (e.g., Jennings et al 2001, Kaiser et al 2002, Hiddink et al 2011, and references therein), including fish condition (e.g., Choi et al 2004, Hiddink et al 2011, Lloret et al 2014. Conversely, positive effects of low levels of trawling have been either hypothesized (e.g., Rijnsdorp et al 1991, Jennings et al 2001, Daan et al 2005 or proved (Hiddink et al 2008, Giacalone et al 2010, Walsh et al 2012, mostly due to removal of the larger specimens and leading to three non-exclusive processes: (1) lower predation rates, resulting in higher benthic prey availability, (2) reduced competition among benthic fauna over food and space, which leads to increases in the production of the small benthos that fish feed on, and (3) proliferation of smaller, more productive benthic species (''farming the sea'').…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also support for this theory from scientists (Hiddink et al, 2008) who show that certain levels of bottom trawling disturbance may enhance the production of food for plaice (small invertebrates), although a recent study suggested that fish condition was negatively related to trawling intensity (Hiddink et al, 2011). The fishermen argue that they are now actually an important part of the ecosystem itself working to enhance marine productivity.…”
Section: Role Of Science In Settling the Debate Among Stakeholdersmentioning
confidence: 96%